Effect of Supercritical CO2 Fluid on Mechanical Properties of Hemp Fibers - Harrabi L,; Almuhamed R,; Drean JY, (Science and Technology - Recent Updates and Future Prospects Vol. 4, 2024)
Hemp fibers have gained increasing attention these last years for their diverse applications, ranging from textiles to construction materials. However, the conventional methods of processing hemp fibers often involve harsh chemicals and high energy consumption, posing environmental concerns. In this context, the utilization of supercritical CO2 (scCO2) technology presents a promising alternative due to its environmentally friendly nature. This study aims to assess the efficiency of this technology for the pretreatment of hemp fiber materials, with a focus on evaluating fiber quality improvements. The obtained results show a promising quality of hemp fibers after this specific pretreatment, especially in the presence of a swelling agent. The scCO2 treatment appeared to remove non-cellulosic compounds from the fiber, thereby resulting in an improvement in its appearance and a decrease in its linear density. We should continue this investigation through further studies since it is an environmentally benign process.